Maresin: Macrophage Mediator for Resolving Inflammation and Bridging Tissue Regeneration—A System-Based Preclinical Systematic Review - Liu, Wen-Chun; Yang, Yu-Hsin; Wang, Yu-Chin; Chang, Wei-Ming; Wang, Chin-Wei (International journal of molecular sciences, 2023)
Maresins are lipid mediators derived from omega-3 fatty acids with anti-inflammatory and pro-resolving properties, capable of promoting tissue regeneration and potentially serving as a therapeutic agent for chronic inflammatory diseases. The aim of this review was to systematically investigate preclinical and clinical studies on maresin to inform translational research. Two independent reviewers performed comprehensive searches with the term “Maresin (NOT) Review” on PubMed. A total of 137 studies were included and categorized into 11 human organ systems. Data pertinent to clinical translation were specifically extracted, including delivery methods, optimal dose response, and specific functional efficacy. Maresins generally exhibit efficacy in treating inflammatory diseases, attenuating inflammation, protecting organs, and promoting tissue regeneration, mostly in rodent preclinical models. The nervous system has the highest number of original studies (n = 25), followed by the cardiovascular system, digestive system, and respiratory system, each having the second highest number of studies (n = 18) in the field. Most studies considered systemic delivery with an optimal dose response for mouse animal models ranging from 4 to 25 μg/kg or 2 to 200 ng via intraperitoneal or intravenous injection respectively, whereas human in vitro studies ranged between 1 and 10 nM. Although there has been no human interventional clinical trial yet, the levels of MaR1 in human tissue fluid can potentially serve as biomarkers, including salivary samples for predicting the occurrence of cardiovascular diseases and periodontal diseases; plasma and synovial fluid levels of MaR1 can be associated with treatment response and defining pathotypes of rheumatoid arthritis. Maresins exhibit great potency in resolving disease inflammation and bridging tissue regeneration in preclinical models, and future translational development is warranted.